Protein Phosphatase PP1 Negatively Regulates IRF3 in Response to GCRV Infection in Grass Carp (Ctenopharyngodon idella) - Hu, Xudong; Wang, Bing; Feng, Haohao; Zhou, Man; Lin, Yusheng; Cao, Hong (Frontiers in Immunology, 2021)
Protein phosphatase-1 (PP1) has an important role in many cell functions, such as cell differentiation, development, immune response and tumorigenesis. However, the specific role of PP1 in the antiviral response in fish remains to be elucidated. In this study, the PPP1R3G homolog was identified in the grass carp (Ctenopharyngodon idella) and its role in defence against the GCRV infection was investigated. Phylogenetic analysis demonstrated that CiPPP1R3G clustered with homologues from other teleosts. Temporal expression analysis in vivo revealed that the expression level of CiPPP1R3G was signiﬁcantly up-regulated in response to GCRV infection in grass carps, especially in the intestine and head-kidney. Cellular distribution analysis revealed that CiPPP1R3G was located in the nucleus and cytoplasm. Overexpression of CiPPP1R3G significantly negatively regulated the expression of CiIRF3, thus inhibiting its activation. In summary, we systematically analyzed the PPP1R3G gene in grass carp and illustrated its function as a negative regulator in the anti-GCRV immune responses.